Effect of platelet rich plasma coating and Chlorella vulgaris 5% ointment on bone implant contact formation after dental implantation: Pengaruh pelapisan platelet rich plasma dan salep Chlorella vulgaris 5% terhadap pembentukan bone implant contact pasca pemasangan implan gigi - Ramli, Rizkiani Awaliyah; Sabirin, Iswanto; Machmud , Edy; Jubhari, Eri Hendra (Makassar Dental Journal PDGI Makassar, 2025)
Platelet rich plasma (PRP) can facilitate implant osseointegration as it functions in the bone healing process. Chlorella vulgaris creates an intracellular bioactive substance called chlorella growth factor (CGF) that can promote bone growth. This study dis-cusses PRP coating and CV 5% ointment on the formation of bone-implant contact (BIC) after dental implant placement in a labo-ratory experiment with a quasi-experimental post-test group design. The samples were 12 implant-placed tooth sockets from 2 male Landrace pigs divided into 2 groups: 5% CV ointment and PRP coating. SEM photographs were taken on day 22 postim-plantation. The sig value of 0.018 was less than α, so there was a significant difference between the BIC of the implants coated with PRP and CV 5%. PRP as a coating on the implant surface can stimulate the bone remodeling process. CV 5% as a bioactive material injected into the socket before implant placement can stimulate the growth and development of fibroblasts and is antipro-teolytic and stimulates tissue formation. It is concluded that PRP coating and 5% CV ointment have effect on the process of BIC formation after dental implant placement.